The role of temperature and drive current in skyrmion dynamics - Litzius, Kai; Leliaert, Jonathan; Bassirian, Pedram; Rodrigues, Davi; Kromin, Sascha; Lemesh, Ivan; Zazvorka, Jakub; Lee, Kyu-Joon; Mulkers, Jeroen; Kerber, Nico; Heinze, Daniel; Keil, Niklas; et al. (Nature Electronics, 2020)
Magnetic skyrmions are topologically stabilized nanoscale spin structures that could be of use in the development of future spintronic devices. When a skyrmion is driven by an electric current it propagates at an angle relative to the flow of current—known as the skyrmion Hall angle (SkHA)—that is a function of the drive current. This drive dependence, as well as thermal effects due to Joule heating, could be used to tailor skyrmion trajectories, but are not well understood. Here we report a study of skyrmion dynamics as a function of temperature and drive amplitude. We find that the skyrmion velocity depends strongly on temperature, while the SkHA does not and instead evolves differently in the low- and high-drive regimes. In particular, the maximum skyrmion velocity in ferromagnetic devices is limited by a mechanism based on skyrmion surface tension and deformation (where the skyrmion transitions into a stripe). Our mechanism provides a complete description of the SkHA in ferromagnetic multilayers across the full range of drive strengths, illustrating that skyrmion trajectories can be engineered for device applications.
CRIS-Team Scopus Importer:2023-03-27